(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2025)
The digital transition has radically transformed the atelier of the contemporary composer, leading to the emergence of a new “digital documentality”. This change necessitates a renewal of musicological research methodologies concerning contemporary creative practices. This paper presents the preliminary findings of an ethnographic fieldwork conducted at Christopher Young’s studio, highlighting the need to consider both documents and production practices. This approach has led to the development of an eclectic study methodology that integrates archival work with the investigation of oral histories, utilising a wide range of documentary sources and leading to a redefinition of the inquiry method. Despite the difficulty of replicating such a large-scale study, both synchronically and diachronically, we believe this research can provide meaningful methodological guidance for musicology concerned with source criticism in contemporary productions. Field observations focused on the music production of Christopher Young’s team for three films: The Autopsy (David Prior, 2022), The Offering (Oliver Park, 2023), and The Piper (Erlingur Thoroddsen, 2023). Fieldwork revealed how music teams integrate digital technologies into the compositional process with original technical, experimental, and creative solutions. The flexibility introduced by the digital transition represents one of the most significant challenges for contemporary musicological research on film music interested in reconstructing the compositional process.